Model Numerik 1D Penggerusan Endapan di Mulut Muara dengan Metode Beda Hingga - Dalrino - -; Mukhlis - -; Elvi Roza Syofyan (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
Sedimentation at estuary river have potency to cause floods because the narrowing of estuary as outlet. Sedimentation process can be caused by the so small river discharge at dry season so that cannot to flushing the sediment that happened at estuary mouth. When the rains arrive, river discharge which starting to big shall no long castaway to sea freely, so that causes floods in headwaters. Numerical simulation by using finite different method with Preissmann implicit scheme conducted to see ability of river discharge in early the rains to flushing the sediment in estuary mouth. Simulation was done at river with sediment elevation at + 4.00 m in estuary mouth. Boundary condition in the form of discharge hydrograph in early the rains at upstream boundary and also critical water surface elevation in sediment top and sea level at downstream boundary applied at model to see behavior of sediment transport and change of profile at bottom channel that happened. Simulation result show with 24 hours floods charge in early the rains, sediment volume of flushed equal to 20,52 %, with elevation reside at + 3,179 m. Sediment will fully under sea-water face after 9 days simulation. Change of upriver discharge and tidal elevation at downstream will influence to speed of stream that happened. By the end of simulation, the bottom profile of channel influenced of tide.